Pregnancy outcomes after fetal exposure to antithyroid medications or levothyroxine. (October 2016) - Schurmann, Lene; Hansen, Anne Vinkel; Garne, Ester
Abstract: Aim: To investigate whether fetal exposure to antithyroid drugs (ATD) and levothyroxine affects gestational age (GA), birth weight, birth length, head circumference and prevalence of congenital anomalies. Methods: Cohort of all pregnancies from GA 12 weeks recorded in Danish registries from 1995–2010. Exposure was having a prescription for ATD or levothyroxine from 91 days before to 91 days after pregnancy start (n = 8318). The reference group was pregnant women without exposure of ATD or levothyroxine (n = 969 303). A subpopulation was linked to the Danish EUROCAT congenital anomaly register. Results: Overall 0.66% of the pregnant women had a prescription for levothyroxine and 0.19% had a prescription for ATD during the exposure period. There was no difference in proportion of live births compared to non-exposed pregnancies, but infants exposed to ATD were more often born very preterm (1.99% versus 0.94% Odds Ratio 2.04, 95% CI 1.46 – 2.86) and had higher infant mortality (Odds ratio 2.37, 95% CI 1.42 – 3.94). Infants exposed to ATD were more likely to have low birth weight and length for GA (Odds ratios 1.29 (1.12 – 1.50) and 1.40 (1.17 – 1.66). There was no difference in head circumference for the 3 exposure groups. Prevalence of congenital anomalies was the same for exposed and non-exposed pregnancies. Conclusion: Fetal exposure to ATD resulted in lower GA, birth weight, length and higher infant mortality. Treatment for hypothyroidism had no significant impact on these variables. There was no difference in prevalence of congenital anomalies. Highlights: Pregnant women with medical treatment for a thyroid disease are older and have higher parity compared to the background population. The infants of mothers treated for hyperthyroidism have lower GA, BW and birth length and higher infant mortality. The treatment of hypothyroidism had no significant impact on these outcomes. The infants had no increased mortality compared to the control population with no exposure. There was no evidence of an increased risk of major congenital anomalies after exposure with ATD or levothyroxine in our population.